Neutralizing Antibody Response by Inactivated SARS-CoV-2 Vaccine on Healthcare Workers - Nataniel Tandirogang; Evi Fitriany; Nursaci Mardania; Miftahul Jannah; Bilqis Faiqotun Nabilah Dilan; Sapta Rahayuning Ratri; Arfian Deny Prakoso; Meiliati Aminyoto; Yuliana Kartika Ningrum; Ika Fikriah; Yadi Yadi (Cell and BioPharmaceutical Institute, 2023)
Background: Currently, the key to combat coronavirus disease 2019 (COVID-19) as a global pandemic is relying mainly on vaccination, and several factors might affect the level of protection. This study aimed to determine the quantitative increase of neutralizing antibody titer against COVID-19 and the influence of gender, body mass index (BMI), routine consumption of vitamin C, D, and E towards the neutralizing antibodies after vaccination. Materials and methods: One hundred nine health workers from various health facilities were recruited. Sinovac inactivated severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) vaccine was used in this study. Antibody titer measurements were carried out quantitatively using electrochemiluminescence immunoassay (ECLIA) on day 14 after the first and second doses administration of the vaccine. Results: The average of antibody titers after the first and second doses were 109.1 and 191.6 U/mL, respectively. Antibody titer significantly increased (p=0.000) as much as 82.5 U/mL from the first to the second dose. There was a significant difference in the increase in antibody titer between respondents who consumed vitamin E regularly and those who did not (p=0.036). Routine consumption of vitamin C and D, gender, and BMI did not affect the increase in neutralizing antibody titer with p-values of 0.983, 0.337, 0.186, and 0.424, respectively. Conclusion: Routine consumption of vitamin E is associated with post-SARS-CoV-2 vaccination neutralizing antibody response. Gender, BMI, and the routine consumption of vitamin C and D have no association with the immune response. Keywords: COVID-19, neutralizing antibody, inactivated SARS-CoV-2 vaccine